Orodispersible ticagrelor use in acute coronary syndrome patients: the Ticagrelor Administered as Standard Tablet or orodispersiblE foRmulation (TASTER) Study. (25th November 2020) - Parodi, G; Talanas, G; Mura, E; Corda, G; Dossi, F; Canonico, M.E; Guarino, S; Nusdeo, G; Franca, P; Raccis, M; Pisano, M; Sanna, G.D; et al.
Abstract: Background: Orodispersible tablet (ODT) is a different tablet formulation that disperse upon contact with the moist mucosal surfaces of the oral cavity and quickly release its components before swallowing; thus drug dissolution and absorption, as well as onset of clinical effect, can be obtained conveniently easily and quickly. Recently, Ticagrelor 90 mg ODT has become available and bioequivalence studies on healthy volunteers documented its effectiveness with consequent approval by the European Medicine Agency. It is unknown whether Ticagrelor ODT might be an effective route of drug administration in high-risk acute coronary syndrome (ACS) patients. Purpose: The aim of the present study is to evaluate the superiority in platelet inhibition with 180 mg Ticagrelor loading dose (LD) administered as ODT as compared with standard (coated table) Ticagrelor formulation, among 130 ACS patients undergoing PCI. Methods: Patients presenting within STEMI or very high-risk NSTEMI referred for immediate (<2 hours) angiography were randomly assigned to receive ODT or standard ticagrelor LD. Platelet reactivity was assessed by Platelet Reactivity Units (PRU) VerifyNow 1, 2, 4 and 6 hours after ticagrelor LD. The primary study endpoint was residual platelet reactivity 1 hour after Ticagrelor LD. Safety endpoints were major bleedings and other in-hospital ticagrelor administration-related adverse events across the two different regimens of Ticagrelor administration. Potential morphine-ticagrelor interaction was assessed by stratified randomization according to morphine use. An interim analysis was planned after the enrollment of 50% (n=65 patients) of the entire study population. The study was supported by an unrestricted grant from AstraZeneca. Results: At the interim analysis, the 2 study group were well matched according to all the baseline characteristics (such as age, sex, diabetes mellitus, chronic renal failure, STEMI at presentation, Killip class, multivessel disease, number of stents implanted, and morphine use). Main pharmacodynamic data are depicted in Figure 1. One hour after LD, PRU (97±99 vs 115±92; p=0.40) was numerically lower, but not statistically different, in the ODT group as compared to standard ticagrelor group. The percentage of platelet inhibition was 55±44% vs 42±44% (p=0.21) in the 2 groups. No significant difference was observed between patients receiving ODT or standard ticagrelor LD regarding in-hospital adverse events or drug side-effects. The study enrollment is ongoing, and final results will be presented at the Congress. Conclusions: ODT administration might represent the most convenient way of treating lying supine ACS patients in the ambulance, emergency room or on the cath lab. Moreover, in patients with difficulties in swallowing ODT represent an easy way of ticagrelor administration. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): AstraZeneca S.P.A.